Topics, Conventions and Styles in the Design of the New Family of Costa Rican Banknotes 2009-2019 as an Expression of Ideology and Coloniality - Andrade Cambronero, Grettel (2019)
This article analyzes Costa Rican banknotes as an expression of ideology and coloniality. The styles and conventions of old Costa Rican numismatic pieces are observed in a semiotic analysis around the axes that we mentioned before. Currently banknotes circulating in Costa Rica are evidence of these ideological aspects. This essay is a consideration on the relationship between design, the identity and ideology.